'Triobaker' / Muhamad Amirul Addin Abd Ghani...[et al.] - Abd Ghani, Muhamad Amirul Addin; Ahmad, Alif Syahin; Mohd Zulkiflee, Mohd Aiman Mirza; Ishak, Nur Alisya
The Headquarter of Duton Enterprise will be in Puncak Alam, Selangor. The business concept is to build automatic bread baker machine. Our product uses the latest technology to apply the best quality for bread baker machine. Triobaker product is totally different with others because we pay much attention to the quality of output bread. In addition, Triobaker product base on the quality of output bread and The process in this machine can reduce time but still can give a good quality product. Besides that, Triobaker product also provides some features to make sure this product as multifunction product properly and based on customer requirement. The features we provide Machine are attached with a dough processing with the right amount of ingredient, A baking and frying area that can suit with a large amount of dough, Easy to use control panel that come with manual instruction and the last is Moveable and easy to handle the machine without complicated instruction. Furthermore, our company also provides services that are product's maintenance and life time warranty.